Pengaruh Reaksi Pasar, Manajemen Laba, dan Audit Delay Terhadap Ketepatan Waktu Pelaporan Keuangan pada Perusahaan Subsektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia - Anisyha Wiendha Antoro; Ratna Anggraini; Aji Ahmadi Sasmi (Indo Publishing, 2026)
This study aims to examine and understand relationship between market reaction, earnings management, and audit delay on the timeliness of financial reporting. The population of this study consists of food and beverage subsector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The sampling technique used in this study is purposive sampling, resulting in 162 observations. Data analysis was conducted using logistic regression analysis and processed with SPSS version 25. The results of this study indicate that market reaction and earnings management do not have a significant effect on the timeliness of financial reporting, while audit delay has a negative effect on the timeliness of financial reporting. These findings suggest that market reaction and earnings management are not the main factors in determining the timeliness of financial reporting. Meanwhile, audit delay indicates that companies experiencing higher levels of audit delay tend to have lower levels of timeliness in financial reporting. This study provides practical implications for companies, auditors, and stakeholders to enhance the efficiency of financial reporting and audit processes to ensure timely reporting in compliance with regulatory requirements.